Islamic Education Curriculum In The Concept Of Tarbawi Hadith And Its Urgency - Nurhadi; Ilyas Husti; Maralottung Siregar (CV. AFDIFAL MAJU BERKAH, 2023)
The purpose of this study is to discuss and describe the curriculum of Islamic education in the concept of hadith Tarbawi. This research method uses library research. As for the results of this study, the curriculum in the concept of Tarbawi hadith is the goal of Islamic education, namely piety, faith, and noble character. While Islamic education materials are faith education, worship education, and moral education. As for the method of Islamic education is the lecture method. Then the evaluation of Islamic education includes the cognitive, affective, and psychomotor domains even though the implementation is still simple according to the needs at that time.